ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA BERDASARKAN LANGKAH POLYA PADA KELAS X MIA SMA PEMBANGUNAN LABORATORIUM UNP - Rohadatul Aysi (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical problem solving is0the main goal and tool in mathematics learning. The fact show that students in class X MIA 1 SMA Pembangunan Laboratorium UNP have made mistakes in solving math problem solving. This study purposes to determine the  most  dominant type of error and causal factors in solving mathematical problem solving based on steps Polya. This research uses a descriptive method wih a quantitative approach. Research subject is 24 students of class X MIA 1 SMA Pembangunan Laoratorium UNP. Data obtained from observation, test, and interview. The result showed that the most dominant type of mistakes made by student were mistakes in carrying out the plan at 47.50%. The cause of the error is the lack of accuracy in using data and calculations, they don’t consider it important a few steps, not mastering the material well, lack of training, and have low intellectual ability. Keywords — Error Analysis, Mathematical Problem Solving, Polya Steps